2016
DOI: 10.1002/hep.28410
|View full text |Cite
|
Sign up to set email alerts
|

Gab1 adaptor protein acts as a gatekeeper to balance hepatocyte death and proliferation during acetaminophen‐induced liver injury in mice

Abstract: Acetaminophen (APAP) overdose is the leading cause of drug-induced acute liver failure. In APAP-induced acute liver failure, hepatocyte death and subsequent liver regeneration determines the prognosis of patients, making it necessary to identify suitable therapeutic targets based on detailed molecular mechanisms. Grb2-associated binder 1 (Gab1) adaptor protein plays a crucial role in transmitting signals from growth factor and cytokine receptors to downstream effectors. In this study, we hypothesized that Gab1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…In the present study, our data showed that STAT3/Erk signaling transductions were activated, as evidenced by increased p-STAT3 and p-Erk1/2 expression. Consistent with previous reports 37 - 38 , our work also suggested that the mitogenic signaling transduction of Erk was also induced in control and liposN groups in APAP-induced acute liver injury. Meanwhile mTOR signaling transduction was activated in total liver extracts by liposIA as evidenced by increased p-mTOR (S2448), upstream protein p-Akt as well as two substrates p-p70s6K (S371) and p-4EBP1-pT45.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, our data showed that STAT3/Erk signaling transductions were activated, as evidenced by increased p-STAT3 and p-Erk1/2 expression. Consistent with previous reports 37 - 38 , our work also suggested that the mitogenic signaling transduction of Erk was also induced in control and liposN groups in APAP-induced acute liver injury. Meanwhile mTOR signaling transduction was activated in total liver extracts by liposIA as evidenced by increased p-mTOR (S2448), upstream protein p-Akt as well as two substrates p-p70s6K (S371) and p-4EBP1-pT45.…”
Section: Discussionsupporting
confidence: 93%
“…Although at 6 h post APAP administration p-JNK levels were not affected by Fibapo these were significantly reduced by 10 h ( Figure 2c ). Concomitantly, increased activation of extracellular signal-regulated kinase 1/2 (ERK1/2), considered part of the compensatory pro-regenerative signaling triggered by APAP toxicity, 39 , 43 was observed in Fibapo-treated mice ( Figure 2d ). Expression of Bcl-xL , an inhibitor of mitochondrial-dependent cell death involved in hepatoprotection from APAP-induced injury, 14 , 42 was enhanced upon Fibapo treatment ( Figure 2e ).…”
Section: Resultsmentioning
confidence: 99%
“…Gab1β expression also increased LIFR-mediated Erk and Akt phosphorylation, directly implicating the adaptor as a transducer of LIFR signals. PI3K/Akt signalling has been shown to be involved in Gab1-mediated cell survival, and in ESCs, activation of this pathway has been reported to promote cell growth, survival and self-renewal ( Cherif et al, 2015 ; Fan et al, 2016 ; Fukumoto et al, 2009 ; Furuta et al, 2016 ; Hishida et al, 2015 ; Holgado-Madruga and Wong, 2003 ; Holgado-Madruga et al, 1997 ; Jirmanova et al, 2002 ; Paling et al, 2004 ; Sun et al, 2014 ; Watanabe et al, 2006 ). By contrast, Erk activation is normally associated with ESC differentiation, and inhibition of Mek-Erk signalling promotes ESC self-renewal ( Burdon et al, 1999 ; Ying et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%